Strategi Peningkatan Ketahanan Pangan Masyarakat Melalui Pelatihan dan Penerapan Teknologi Aquaponik di Desa Tetebatu - Putra, Agus Muliadi; Husnayati Hartini; Muhammad Iman Darmawan; Baiq Liana Widiyanti; Shofwatunnida’ Septarini (Universitas Hamzanwadi, 2025)
The increasing issue of global climate change and population growth also pose new challenges in meeting the food needs of the community. Seasonal anomalies and unpredictable weather also disrupt community planting patterns, leading to increases in food commodity prices. One good practice in improving community food security is to implement a fish and vegetable cultivation system often referred to as aquaponics. Considering the size of the area and the optimization of green open spaces, the aquaponics system is considered to be an alternative for utilizing unused yards. The aquaponics training in Tetebatu Village not only focused on knowledge transfer, but also encouraged a transformation in the community's perspective on modern, environmentally friendly agricultural practices. The training program is divided into three stages: socialization and counseling, technical training, and continuous mentoring. During the mentoring process, several factors are considered influential in maintaining and developing this aquaponics system, including the need for collaboration and innovation with partners and the involvement of all parties, such as the youth community in the digital ecosystem, to support the social and economic sustainability of the program. In addition to being environmentally friendly, aquaponics technology can also strengthen the principles of the circular economy in communities. The successful implementation of aquaponics technology in Tetebatu Village, which is a low-cost, high- impact initiative, is clear evidence that technological transformation and innovation based on local communities can be a concrete step towards sustainable development.